أهمية إستخدام تكنولوجيات المعلومات و الإتصال في تطوير أداء المورد البشري - عفاف عباس سراندي; هاجر مسعودي; الرميصاء جديدي (جامعة الوادي university of eloued, 2024)
"تهدف هذه الدراسة للبحث في أهمية استخدام تكنولوجيات المعلومات والاتصال وأثرها في تطوير أداء المورد البشري لمؤسسة اتصالات الجزائر الوادي، ولتحقيق اهداف الدراسة ثم الاعتماد على المنهج الوصفي التحليلي، ولجمع البيانات قمنا بإعداد وتوزيع الاستبيان على المؤسسة تم استرجاع 100 استبانة صالحة للتحليل، وبعد جمع البيانات التي جاءت بها الاستمارة والمدرجة في برنامج (SPSS) والتطرق إلى المنهجية والأدوات المستخدمة في الدراسة الميدانية، وتحليل وتفسير النتائج المتوصل إليها ومعالجتها، وإختبار صحة فرضيات الدراسة التي تم وضعها في مقدمة الدراسة، تم التوصل إلى النتائج التالية: يوجد استعمال تكنولوجيات المعلومات والاتصال في المؤسسات الاقتصادية الجزائرية. توجد ضرورة لاستخدام تكنولوجيات المعلومات والاتصال. تستخدم المؤسسة الاقتصادية تكنولوجيات المعلومات والاتصال في تطوير أداء المورد البشري تساهم تكنولوجيات المعلومات والاتصال في تطوير أداء المورد البشري في المؤسسة. " "This study aims to investigate the importance of using information and communication technologies and their impact on developing the performance of the human resource of the Algeria Telecom Corporation- El Oued. To achieve the objectives of the study, the descriptive and analytical approach was relied upon. To collect data, we prepared and distributed the questionnaire to the organization, 100 questionnaires suitable for analysis were retrieved, and after collecting the data. Which came in the form and included in the (SPSS) program, and touched on the methodology and took used in the field study, and analyzed and interpreted the results obtained and processed, and tested the validity of the study hypotheses that were put in the introduction to the study, the following results were reached There is the use of information and communication technologies in Algerian economic institutions. There is a need to use information and communication technologies. The economic institution uses information and communication technologies to develop the performance of the human resource. Information and communication technologies contribute to developing the performance of the organization's human resource. "
Keywords: تكنولوجيات المعلومات والإتصال ، الموارد البشرية، أداء الموارد البشرية، تأهيل الموارد البشرية. information and communication technologies; human resources; human resources performance; human resources qualification